Aftermarket Wheels Numerical Simulation To Get Maximum Stress and Deformation Values - Mulyadi Mulyadi; Akhmad Surya Wijianto; Iswanto (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
The purpose of this research is to get wheels with offset variants of -15, +20, and +35 made of aluminum alloy with a maximum load of 690 kg. Autocad 2018 and Unigraphic NX 8 were used to create all three designs. The load was calculated using the SAE J2530 standard and simulated using the ANSYS Workbench 14.5 application's numerical simulation method. As a result, the car rim is designed with a spoke form that becomes steeper (Concave) as the offset decreases. Methods a) Dynamic Cornering Fatigue Test, b) Dynamic Radial Fatigue Test, and c) Impact test consecutively at offset -15 of a) 62.33 MPa, b) 111.61 MPa, and c) 1.58 mm can be used to obtain numerical simulation results. For offsets of +20 of 70.91 MPa, 75.75 MPa, and 1.6 mm. And a) 90.33 MPa, b) 78.13 MPa, c) 1.61 mm at offset +35.